Heresy in Architecture; Is it Real? - Munichy Bachron Edrees (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
Most people who Salafiism holder still assume that what they do should be consist of with prophet Muhammad done, so they always being carefully whenever doing something, because they are extremely afraid if they are doing something not consist of with what Muhammad done, they assume that is bid’ah (heresy) deed. They belief all heresy deviated from Islamic law. So even though constructing some building they always copy what Muhammad done completely. It means they don’t know yet the meaning of heresy is. In accordance with what prophet said, heresy is doing something which is relate with ibadah mahdhoh which is not be done by Prophet Muhammad. Architecture is cultural product so that it is not relate with ibadah. Other ways there is not relation with heresy. So there is no heresy in Architecture.